Sensor pointing verification for the TRMM precipitation radar - Kasparis, Takis; Eubanks, Chris; Jones, Linwood W. (My University, 2000)
The purpose of this paper is to describe an experimental procedure for verifying the navigation data provided by the NASA Goddard Space time Flight Center's Tropical Rainfall Measurement Mission (TRMM) Precipitation Radar (PR). The TRMM PR is a satellite-borne, electronically scanning, range-gated radar that produces 3D images of the structure of atmospheric precipitation. Due to the dynamic nature of precipitation events in space and time, proper collocation is critical to the accuracy of the data
Keywords: Weather radar networks; Meteorological satellites; Goddard Space Flight Center